Contrasting impacts of the 8.2‐ and 4.2‐ka abrupt climatic events on the regional vegetation of the Hulun Lake region in north‐eastern China. (9th July 2020) - Zhang, Shengrui; Xiao, Jule; Xu, Qinghai; Wen, Ruilin; Fan, Jiawei; Huang, Yun; Li, Manyue; Liang, Jian
ABSTRACT: Studies of the vegetation response to abrupt climatic events may provide valuable insights into assessing the impacts of such events under future global warming scenarios. Here we present a detailed record of regional vegetation change based on high‐resolution pollen records for the intervals 9000–7000 and 5000–3000 cal a bp from the Hulun Lake region of north‐eastern China. Our aims were to determine the regional expression of the 8.2‐ and 4.2‐ka events in north‐eastern China, especially their effects on vegetation composition. The results show that the response of the vegetation of the Hulun Lake region to the climatic cooling of the 8.2‐ka event was relatively minor; however, the 4.2‐ka event, which resulted in climatic aridification, resulted in pronounced vegetation degradation. We suggest that the specific characteristics of the 8.2‐ and 4.2‐ka events, together with their duration and the regional climatic background on an orbital time scale, were the main factors responsible for the contrasting vegetation responses. The strengthening and northward shift of the Intertropical Convergence Zone (ITCZ) tended to offset the cooling effect of the 8.2‐ka event on regional vegetation in the mid–high latitudes of East Asia; in contrast, the decrease in summer insolation in the Northern Hemisphere and the southward shift of the ITCZ may have intensified the drought effect of the 4.2‐ka event in East Asia and the associated vegetation degradation. Under future global warming scenarios, both extreme cooling events and extreme drought events may cause a deterioration of the ecological environment; however, the resulting regional vegetation responses may be substantially different.